Sports management of the municipality of Cogua for the construction of a public policy (2019)
Sports and recreational management in the municipality of Cogua depends on government funding and the sponsorship received, requires a series of basic skills such as: leadership, communication, problem solving, decision making, time management, among others. In this order of ideas, it is the responsibility of the sports organization and the process leader, to ensure that it is managed in an adequate and efficient manner, thus contributing to strengthen social ties, modify lifestyles, achieve sports results, reduce indicators of violence and consumption of psychoactive substances, in order to meet the needs of the population.